PENGEMBANGAN PLOTCAP EDUVID MATERI PENGAMALAN NILAI-NILAI PANCASILA PADA SIKAP DAN PERILAKU BERMASYARAKAT DI KELAS IV SEKOLAH DASAR NEGERI SUKAREJO - Wirdah Assidikia, Haya; Rapita Aprilia; Inge Ayudia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Providing learning media that match the characteristics of elementary school students is essential to support meaningful learning in Pancasila Education. The topic of implementing Pancasila values in social life requires instructional media that present learning experiences in a concrete and contextual manner. This study was conducted to develop Plotcap Eduvid and evaluate its validity and practicality prior to classroom implementation. A Research yand Development (R&D) method was employed using the 4D development model, which consists of the Define, Design, Develop, and Disseminate stages. The participants involved one material expert, one media expert, one language expert, one fourth-grade teacher, and 31 fourth-grade students at SDN Sukarejo. Data were obtained through expert validation sheets and response questionnaires, and subsequently analyzed using descriptive quantitative techniques based on percentage scores. The validation process resulted in scores of 98.21% from the material expert, 81.25% from the media expert, and 82.50% from the language expert, indicating that the developed media was highly valid. Practicality testing also demonstrated highly positive responses from both the teacher and the students. These findings indicate that Plotcap Eduvid is suitable for use as a supporting instructional medium for teaching the implementation of Pancasila values in fourth-grade elementary schools.